Penerapan Manajemen Berbasis Buddhis Dalam Toleransi Kehidupan Beragama Pada Umat Vihara Prajna Maitreya Sungai Raya Kubu Raya - Edy Edy; Sonika Sonika (Jurnal Maitreyawira, 2024)
This study aims to find out how the Implementation of Buddhist-Based Management in Tolerance of Religious Life in the Prajna Maitreya Sungai Raya Kubu Raya Temple's Congregation Data collection techniques with observation, interviews, documentation, and triangulation. Data analysis techniques with interactive models (Miles and Huberman, 1994: 12), through data reduction, data presentation, and conclusion/verification. The validity of the data is carried out by validating concepts in the form of triangulation and member checks. From the results of the research that the application of Buddhist-based management is more about implementing self-management in good behavior, being polite, being able to yield and being patient in solving every problem to create a peaceful, harmonious and harmonious life so as to create a high sense of tolerance in religious life.